HSC senescence upon irradiation - Geiger, Hartmut (American Society of Hematology, 2014)
In this issue of Blood, Shao et al report that a side effect of total body irradiation (TBI) is long-term bone marrow injury and thus dysfunctional hematopoiesis caused by the induction of hematopoietic stem cell (HSC) senescence. Interestingly and unexpectedly, however, this happens in a manner independent of the cell-cycle regulators Ink4a and Arf, which play a major role in senescence in other cell systems.(1)